1979
DOI: 10.1038/281069a0
|View full text |Cite
|
Sign up to set email alerts
|

A physiological correlate of disuse-induced sprouting at the neuromuscular junction

Abstract: Recent investigations have established that many of the normal properties of muscle fibres are maintained, at least in part, by muscle activity. Thus, a fall in resting membrane potential, an increase in input resistance, and spread of acetylcholine receptors to extrajunctional sites can all be induced by abolishing muscle activity and prevented by direct stimulation of denervated muscle fibres. Muscle activity also exerts a trophic influence on the innervating motoneurones; furthermore it may be a factor in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 14 publications
4
29
1
Order By: Relevance
“…1 A). This observation was surprising, given previous reports of increases in quantal contents after block of nerve activity with TTX (Snider and Harris, 1979;Tsujimoto and Kuno, 1988;Tsujimoto et al, 1990). However, previous studies were performed with endplates bathed in solution containing low external Ca 2ϩ -raised Mg 2ϩ , and, when we reproduced those conditions, we found a significant increase in quantal content ( Fig.…”
Section: Resultscontrasting
confidence: 42%
See 3 more Smart Citations
“…1 A). This observation was surprising, given previous reports of increases in quantal contents after block of nerve activity with TTX (Snider and Harris, 1979;Tsujimoto and Kuno, 1988;Tsujimoto et al, 1990). However, previous studies were performed with endplates bathed in solution containing low external Ca 2ϩ -raised Mg 2ϩ , and, when we reproduced those conditions, we found a significant increase in quantal content ( Fig.…”
Section: Resultscontrasting
confidence: 42%
“…More than 25 years ago, it was shown that block of activity at the mammalian neuromuscular junction in vivo increased synaptic strength (Snider and Harris, 1979;Tsujimoto and Kuno, 1988;Tsujimoto et al, 1990). Recent studies have found that a similar increase in synaptic strength occurs after block of activity at synapses between neurons (Manabe et al, 1989;Webb and Cope, 1992;Davis and Bezprozvanny, 2001;Burrone and Murthy, 2003;Turrigiano and Nelson, 2004).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These sprouts add or restore synaptic contacts on inactive (Snider and Harris, 1979,Angaut-Petit et al, 1990,Meunier et al, 2002 or denervated muscle fibers, which improve the motor deficits associated with peripheral nerve injury (Brown et al, 1981,Wernig and Herrera, 1986,Tam and Gordon, 2003a or spinal cord injury (Yang et al, 1990,Marino et al, 1994,Thomas et al, 1997. Despite its significance for repair of the adult nervous system, the molecular and cellular events leading to the compensatory process remain elusive.…”
Section: Introductionmentioning
confidence: 99%